Re-Examining the Earnings Assimilation of Immigrants - Taryn Ann Galloway (Statistics Norway, Research Department, 2008)
Studies on the earnings assimilation of immigrants have traditionally focused exclusively on immigrants in employment. However, given evidence of immigrants' difficulties in entering and remaining in the labor market, restricting the population to those in employment may entail a selection bias. In addition, the primary variable of interest in such studies is often the duration of residence or the years since migration (YSM), which is interpreted as a proxy for potential labor market experience in the host country. The appropriateness of that proxy will, however, also depend on the extent to which immigrants are able to quickly enter and remain in the labor market. This study thus re-examines evidence on the earnings assimilation of immigrants in light of selection into the labor market and with better information on actual labor market experience in the host country. The findings suggest that a major revision of previous conclusions about the earnings assimilation of immigrants in Norway may be in order.
Keywords: J20; 330; Immigration; assimilation; employment; earnings